High-throughput micro-nanostructuring by microdroplet inkjet printing - Hendrikje R. Neumann (Beilstein Journal of Nanotechnology, 2018)
The production of micrometer-sized structures comprised of nanoparticles in defined patterns and densities is highly important in many fields, ranging from nano-optics to biosensor technologies and biomaterials. A well-established method to fabricate quasi-hexagonal patterns of metal nanoparticles is block copolymer micelle nanolithography, which relies on the self-assembly of metal-loaded micelles on surfaces by a dip-coating or spin-coating process. Using this method, the spacing of the nanoparticles is controlled by the size of the micelles and by the coating conditions. Whereas block copolymer micelle nanolithography is a high-throughput method for generating well-ordered nanoparticle patterns at the nanoscale, so far it has been inefficient in generating a hierarchical overlay structure at the micrometer scale. Here, we show that by combining block copolymer micelle nanolithography with inkjet printing, hierarchical patterns of gold nanoparticles in the form of microstructures can be achieved in a high-throughput process. Inkjet printing was used to generate droplets of the micelle solution on surfaces, resulting in printed circles that contain patterns of gold nanoparticles with an interparticle spacing between 25 and 42 nm. We tested this method on different silicon and nickel–titanium surfaces and the generated patterns were found to depend on the material type and surface topography. Based on the presented strategy, we were able to achieve patterning times of a few seconds and produce quasi-hexagonal micro-nanopatterns of gold nanoparticles on smooth surfaces. Hence, this method is a high-throughput method that can be used to coat surfaces with nanoparticles in a user-defined pattern at the micrometer scale. As the nanoparticles provide a chemical contrast on the surface, they can be further functionalized and are therefore highly relevant for biological applications.